2000
DOI: 10.1007/s004310050022
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency and early-onset liver cirrhosis in two siblings

Abstract: Liver cirrhosis and brain damage may be underestimated in cases of long-chain 3-hydroxyacyl-coenzyme A dehydrogenase deficiency and may occur early in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…They were attributed to hypoglycaemia that was apparently due to inadequate diet therapy. As previously reported (12), our patient developed portal brosis. The exact onset of such brosis cannot be determined since liver biopsy had not been performed before the age of 3 mo.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They were attributed to hypoglycaemia that was apparently due to inadequate diet therapy. As previously reported (12), our patient developed portal brosis. The exact onset of such brosis cannot be determined since liver biopsy had not been performed before the age of 3 mo.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, death was attributed to the liver involvement in only 6 cases (2 cases of Reye syndrome and 4 with possible liver failure). Van Maldergem et al (12) present two siblings with early-onset cirrhosis (at the age of 2 mo and 6 mo). Death was attributed to liver failure in one case.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality of up to 50% was reported in some series (Sewell et al 1994;Tyni et al 1997b) and usually is about 30% of symptomatic patients (den Boer et al 2002;Spiekerkoetter et al 2009). The deaths of LCHAD-deficient patients were described in the majority of case reports (Dionisi-Vici et al 1990;Duran et al 1991;Jackson et al 1992;Isaacs et al 1996;Van Maldergem et al 2000;Hintz et al 2002) including first descriptions (Wanders et al 1990;Wanders et al 1992;Roe and Coates 1995) and even in newborns identified presymptomatically by NBS (Wilcken et al 2003;Wilcken et al 2009). This study included the large cohort of 59 LCHADdeficient patients diagnosed and followed in one metabolic center.…”
Section: Discussionmentioning
confidence: 93%